Influences of CCK-8 on expressions of apoptosis-related genes in prefrontal cortex neurons of morphine-relapse rats. (19th September 2016) - Ye, Guanghua; Tao, Luyang; Ma, Chunling; Wen, Di; Yu, Linsheng; Fan, Yanyan; Hu, Haiyan; Chen, Xiping; Chu, Yang; Gao, Yuan; Gao, Cheng; Wang, Haochen
Highlights: A morphine-relapse-rat model has been established. CCK-8 significantly attenuated reinstatement of CPP. CCK-8 (0.1 and 1.0 μg, i.c.v) could up-regulate expressions of Bcl-2, down-regulate those of Bax and Caspase-3 and reduce Bax/Bcl-2 ratio. CCK-8 (0.1 and 1.0 μg, i.c.v) could protect neurons by influencing expressions of apoptosis-related genes. Abstract: In order to elucidate the influences of CCK-8 on expressions of apoptosis-related genes, Bax, Bcl-2 and Caspase-3, of prefrontal cortex neurons in morphine-relapse rats, an effective, successful morphine-relapse-rat model using the conditioned place preference (CPP) under CCK-8 (0.01, 0.1 and 1.0 μg, i.c.v) intervention was established. The prefrontal cortexes were made into slices with the cellular plasmas immunohistochemically stained. The expressions of Bax, Bcl-2, Caspase-3 of neurons were evaluated through their scores, and each corresponding ratio of Bax and Bcl-2 (Bax/Bcl-2) was also computed. The results showed that the expression of Bcl-2 was very weak and those of Bax and Caspase-3 were hardly seen in group normal saline; the expressions of Bax and Caspase-3 were strong and that of Bcl-2 was weak in group morphine and compared to group normal saline, there were significant differences ( P  < 0.05); the expressions of Bax, Caspase-3 and the ratios of Bax/Bcl-2 have a gradually-decreased trend in the sequence of group 0.01 μg, group 0.1 μg and group 1.0 μg, but the expression of Bcl-2 has an opposite trend in the same sequence, and compared to group morphine, there were significant differences ( P  < 0.05) excluding group 0.01 μg. So we draw a conclusion that CCK-8 (0.1 and 1.0 μg, i.c.v) could protect neurons of prefrontal cortex through up-regulating the expression of Bcl-2, down-regulating those of Bax and Caspase-3 and reducing Bax/Bcl-2 ratio in the model of morphine-relapse rats.